2018
DOI: 10.1111/liv.13615
|View full text |Cite
|
Sign up to set email alerts
|

ePTFE‐TIPS vs repetitive LVP plus albumin for the treatment of refractory ascites in patients with cirrhosis

Abstract: ePTFE-TIPS results in superior control of ascites without increasing the risk for overt HE as compared to LVP+A. Although ePTFE-TIPS improved 1-year survival in cirrhotic patients with refractory ascites, its use was not independently associated with transplant-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
4
31
1
Order By: Relevance
“…However, the sample size in this study was very low and the patient population was more heterogeneous, since they included patients receiving a TIPS for either RA as well as for variceal bleeding. Bucsics et al identified age as an independent predictor for post-TIPS mortality [37]. The strength of this study was that-in accordance with our study-only covered stent grafts were used.…”
Section: Plos Onesupporting
confidence: 70%
See 1 more Smart Citation
“…However, the sample size in this study was very low and the patient population was more heterogeneous, since they included patients receiving a TIPS for either RA as well as for variceal bleeding. Bucsics et al identified age as an independent predictor for post-TIPS mortality [37]. The strength of this study was that-in accordance with our study-only covered stent grafts were used.…”
Section: Plos Onesupporting
confidence: 70%
“…Remarkably, the role of age as a predictor for survival after TIPS has been controversially discussed in the current literature, so far: Age was identified as a predictor for post-TIPS mortality in some [30][31][32][33][34][35][36][37], but not in all studies [38][39][40][41]. This discordance could be ascribed to methodological dissimilarities between the different studies such as the particular age thresholds for the definition of the 'elderly' population, various sample sizes, the type of stent used or the TIPS indication (RA vs. variceal bleeding).…”
Section: Plos Onementioning
confidence: 99%
“…These results are in line with recent findings from our group, suggesting that sarcopenia is not linked to the severity of portal hypertension, 8 which is a main driver of hepatic decompensation. [26][27][28] Conversely, sarcopenia was a strong risk factor for increased mortality, especially in patients with cACLD, in whom it was independently linked to the outcome of interest. While the median TFS for patients with cACLD and dACLD without sarcopenia was 82 and 60 months, respectively, it was only 54 and 30 months in patients with sarcopenia respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More recently intramuscular testosterone supplementation has been shown to improve muscle mass, although no effect on liver‐related outcomes was observed . Furthermore transjugular intrahepatic portosystemic shunt (TIPS)‐implantation has been shown to potentially reverse sarcopenia and this could be an important early intervention in sarcopenic patients with refractory ascites or variceal bleeding . Nevertheless, the only available data that show an improved survival when overcoming sarcopenia come from trials investigating patients before and after TIPS .…”
Section: Discussionmentioning
confidence: 99%